Testing for the Ratchet Effect: Evidence from a Real-Effort Work Task - Eric Cardella; Briggs Depew (Institute for the Study of Labor (IZA), 2016)
The "ratchet effect" refers to a phenomenon where workers whose compensation is based on productivity strategically restrict their output, relative to their capability, because they rationally anticipate that high levels of output will be met with increased or "ratcheted-up" expectations in the future. While there is ample anecdotal evidence suggesting the presence of the ratchet effect in real workplaces, it is difficult to actually empirically identify output restriction among workers. In this study, we implement a novel experimental design using a real-effort work task and a piece-rate incentive scheme to directly test for the presence of the ratchet effect using two different methods for evaluating productivity: (i) when productivity is evaluated based on the output of each individual worker, and (ii) when productivity is evaluated collectively based on the output of a group of workers. We find strong evidence of the ratchet effect when productivity is evaluated at the individual-level. However, we find very little evidence of the ratchet effect when productivity is evaluated collectively at the group-level. We attribute the latter result to the free-riding incentive that emerges when productivity is evaluated at the group-level. Furthermore, we find the ratchet effect re-emerges if workers are able to communicate. Our experimental design, combined with using a real-effort work task, also allows us to shed light on an important dynamic implication of the ratchet effect that has not yet been examined in the literature – the role of the ratchet effect on future productivity via learning-by-doing.
Keywords: J30; J40; D70; D01; C92; 330; ratchet effect; output restriction; piece-rate pay; real-effort task; learning-by-doing